Advances in oxidation and ablation resistance of high and ultra-high temperature ceramics modified or coated carbon/carbon composites - Jin, X.; Fan, X.; Lu, Chunsheng; Wang, T. (Elsevier Ltd, 2017)
Carbon/carbon (C/C) composites are considered as one of the most promising materials in structural applications owing to their excellent mechanical properties at high temperature. However, C/C composites are susceptible to high-temperature oxidation. Matrix modification and coating technology with ultra-high temperature ceramics (UHTCs) have proved to be highly effective to improve the oxidation and ablation resistance of C/C composites. In this paper, recent advances in oxidation and ablation resistance of C/C composites were firstly reviewed, with attention to oxidation and ablation properties of C/C composites coated or modified with UHTCs. Then, several new methods in improving oxidation and ablation resistance were discussed, such as by using nanostructures to toughen UHTCs coatings or carbon matrix and the combination of matrix modification and coating technology. In addition, relevant ablation tests with scaled models were also briefly introduced. Finally, some open problems and future challenges were highlighted in the development and application of these materials.